Elevated gamma glutamyl transferase levels are associated with the location of acute pulmonary embolism.: Cross-sectional evaluation in hospital setting - Korkmaz, Ozge (2015)
CONTEXT AND OBJECTIVE: The location of embolism is associated with clinical findings and disease severity in cases of acute pulmonary embolism. The level of gamma-glutamyl transferase increases under oxidative stress-related conditions. In this study, we investigated whether gamma-glutamyl transferase levels could predict the location of pulmonary embolism. DESIGN AND SETTING: Hospital-based cross-sectional study at Cumhuriyet University, Sivas, Turkey. METHODS: 120 patients who were diagnosed with acute pulmonary embolism through computed tomography-assisted pulmonary angiography were evaluated. They were divided into two main groups (proximally and distally located), and subsequently into subgroups according to thrombus localization as follows: first group (thrombus in main pulmonary artery; n = 9); second group (thrombus in main pulmo-nary artery branches; n = 71); third group (thrombus in pulmonary artery segmental branches; n = 34); and fourth group (thrombus in pulmonary artery subsegmental branches; n = 8). RESULTS: Gamma-glutamyl transferase levels on admission, heart rate, oxygen saturation, right ventricu-lar dilatation/hypokinesia, pulmonary artery systolic pressure and cardiopulmonary resuscitation require-ment showed prognostic significance in univariate analysis. The multivariate logistic regression model showed that gamma-glutamyl transferase level on admission (odds ratio, OR = 1.044; 95% confidence interval, CI: 1.011-1.079; P = 0.009) and pulmonary artery systolic pressure (OR = 1.063; 95% CI: 1.005-1.124; P = 0.033) remained independently associated with proximally localized thrombus in pulmonary artery. CONCLUSIONS: The findings revealed a significant association between increased existing embolism load in the pulmonary artery and increased serum gamma-glutamyl transferase levels.